Subependymal giant cell astrocytomas in Tuberous Sclerosis Complex have consistent TSC1/TSC2 biallelic inactivation, and no BRAF mutations - Bongaarts, Anika (Oncotarget, 2017)
Subependymal giant cell astrocytomas (SEGAs) are rare, low-grade glioneuronal brain tumors that occur almost exclusively in patients with tuberous sclerosis complex (TSC). Though histologically benign, SEGAs can lead to serious neurological complications, including hydrocephalus, intractable seizures and death. Previous studies in a limited number of SEGAs have provided evidence for a biallelic two-hit inactivation of either TSC1 or TSC2, resulting in constitutive activation of the mechanistic target of rapamycin complex 1 pathway. The activating BRAF V600E mutation is a common genetic alteration in low grade gliomas and glioneuronal tumors, and has been reported in SEGAs as well. In the present study, we assessed the prevalence of the BRAF V600E mutation in a large cohort of TSC related SEGAs (n=58 patients including 56 with clinical TSC) and found no evidence of either BRAF V600E or other mutations in BRAF. To confirm that these SEGAs fit the classic model of two hit TSC1 or TSC2 inactivation, we also performed massively parallel sequencing of these loci. Nineteen (19) of 34 (56%) samples had mutations in TSC2, 10 (29%) had mutations in TSC1, while 5 (15%) had no mutation identified in TSC1/TSC2. The majority of these samples had loss of heterozygosity in the same gene in which the mutation was identified. These results significantly extend previous studies, and in agreement with the Knudson two hit mechanism indicate that biallelic alterations in TSC2 and less commonly, TSC1 are consistently seen in SEGAs.